İnterkostal nevraljinin nadir bir nedeni: Göğüs duvarının ancient schwannoması - (:unkn) unknown (My University, 2017)
İnterkostal nevralji, interkostal sinir boyunca yayılan ağrı ile karakterize nadir bir durumdur. Torasik tümörler çoğunlukla mediasten kaynaklı olup, primer tümörlerin ancak %5-10'dan azı interkostal sinirlerden orijin alır. Bu hastalar genellikle asemptomatik olurlar. Biz burada göğüs duvarı schwannoması nedeniyle ciddi interkostal ağrı ile başvurmuş 42 yaşında bir erkek hastayı sunduk. Cerrahi rezeksiyon sonrası schwannomanın nadir bir türü olan ancient schwannoma tanısı alan hasta, sonrasında ağrısız izlenmiştir.

Intercostal neuralgia is a rare condition that causes pain along the intercostal nerves. Neural tumors of the chest mostly arise from mediastinum and only less than 5-10% of primary tumors originate from intercostal nerves. These patients are usually asymptomatic. Herein, we report a 42-year-old male patient with severe intercostal neuralgia due to the schwannoma of the chest wall. The patient underwent surgical resection and his histopathological diagnosis was a very rare type of schwannoma: ancient schwannoma. Resecting the tumor relieved his pain.
A rare cause of intercostal neuralgia: Ancient schwannoma of the chest wall
Keywords: Genel ve Dahili Tıp; Tıbbi Araştırmalar Deneysel